1996
DOI: 10.1182/blood.v87.10.4149.bloodjournal87104149
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-gamma constitutively expressed in the stromal microenvironment of human marrow cultures mediates potent hematopoietic inhibition

Abstract: Clinical and laboratory studies have suggested involvement of interferon-gamma (IFN-gamma) in the pathophysiology of aplastic anemia. T cells from aplastic anemia (AA) patients secrete IFN-gamma in vitro, activated cytotoxic lymphocytes infiltrate aplastic bone marrow (BM), and IFN-gamma mRNA, not detected in normal BM, is present in BM from most AA patients. Many patients respond to immunosuppressive therapy with antithymocyte globulin and cyclosporine. Using long-term BM cultures (LTBMC) as a tissue culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0
8

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(86 citation statements)
references
References 42 publications
5
73
0
8
Order By: Relevance
“…In our study, no significant difference was observed between the AA patient group and the normal control group in the production index of intracellular IFN-c of BMLs and PBLs, but production index of intracellular IFN-c of CD8 + BMLs in AA patient group had tendency to be higher than in normal control (P ¼ 0.080). Selleri et al reported that high levels of IFN-c were needed to produce an inhibitory effect on hematopoiesis according to long-term culture initiating cell assay (27). Our study seemed to be consistent with previous report, but it is still unclear whether IFN-c is directly involved in the inhibition of hematopoiesis in AA patients.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, no significant difference was observed between the AA patient group and the normal control group in the production index of intracellular IFN-c of BMLs and PBLs, but production index of intracellular IFN-c of CD8 + BMLs in AA patient group had tendency to be higher than in normal control (P ¼ 0.080). Selleri et al reported that high levels of IFN-c were needed to produce an inhibitory effect on hematopoiesis according to long-term culture initiating cell assay (27). Our study seemed to be consistent with previous report, but it is still unclear whether IFN-c is directly involved in the inhibition of hematopoiesis in AA patients.…”
Section: Discussionsupporting
confidence: 91%
“…For example, IFN-␥ may, under certain circumstances (e.g., in case of inhibition of interferon regulatory factor-1 [IRF-1]), induce an aberrant stimulatory effect on hematopoietic progenitors. 59,60 As the absence of IRF-1 has been described in MDS patients, 61 IFN-␥ may provide aberrant stimulatory signals during the expansion of the MDS clone.…”
Section: Discussionmentioning
confidence: 99%
“…The close contact between stroma and HP is likely to maximize the effect of the cytokine on HP proliferation, as observed to occur with the growth-promoting effect of cADPR. Indeed, the steady supply of low concentrations of the cytokine by IFN-γ-transduced feeders has been demonstrated to be far more efficient in inhibiting HP growth than direct addition of the cytokine to the medium (31).…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ is one of the most potent hemopoiesis-inhibiting cytokines known (31). ELISA was used to measure its concentration in the medium conditioned by confluent, irradiated CD38 +/layers cultured for 7 days in LTC medium.…”
Section: Ifn-γ Production By Cd38 + Feedersmentioning
confidence: 99%